THE EFL STUDENTS’ PERCEPTIONS OF THE QUALITY OF THE ENGLISH LANGUAGE TEXTBOOK - Arsen Nahum Pasaribu (University of Kuningan, 2022)
The purpose of this study is to elicit students' perceptions about the quality of English textbook used by Indonesian EFL students. Although numerous teaching researchers have undertaken research on textbooks, it is still uncommon to conduct textbook research to ascertain students' perceptions on the quality of textbooks. This study employed a mixed-methods approach and gathered data from 300 senior high school students in grade eleven. They were chosen at random among 674 students. These students come from SMA 12 Medan and SMK 3 Parulian Medan. Each school was represented by 150 students in the eleventh grade. Google forms were utilized to collect data. Simple statistics are used to calculate the number and percentage in research data analysis, while interactive data analysis is used to examine qualitative data. The results of this study show that the textbook